1979
DOI: 10.1002/ana.410060206
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Hydroxybutyric acid is not a GABA‐mimetic agent in the spinal cord

Abstract: gamma-Hydroxybutyric acid (GHB), a pharmacologically active central nervous system constituent, has been postulated to function as a gamma-aminobutyric acid (GABA) agonist. This hypothesis was tested directly on GABAergic synapses in isolated, superfused frog spinal cord. Addition of GHB to the superfusate produced effects on primary afferent terminals that were distinctly different from the effects of GABA. Thus, although both compounds depressed dorsal root potentials, GHB hyperpolarized terminals while GABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…73 Thus it was suggested that GABA and GHB, produced in the same neuron, are colocalized in the same synaptic vesicles by transport through the vesicular inhibitory amino acids transporter (VIAAT), which is involved in the vesicular loading of both GABA and glycine. Because of the presence of high-affinity binding sites for GHB only in upper brain regions (i.e., outside the brain stem and spinal cord), 74,75 the role of glycine in GABA/GHB neurons was not considered. To summarize, all these data support the existence, in GABAergic pathways, of common mechanisms that cosynthetize and coaccumulate GABA and GHB in presynaptic terminals, resulting in their corelease in mixed GABA/GHB synapses.…”
Section: A Synaptic and Plasma Membrane Transport Of Ghbmentioning
confidence: 99%
“…73 Thus it was suggested that GABA and GHB, produced in the same neuron, are colocalized in the same synaptic vesicles by transport through the vesicular inhibitory amino acids transporter (VIAAT), which is involved in the vesicular loading of both GABA and glycine. Because of the presence of high-affinity binding sites for GHB only in upper brain regions (i.e., outside the brain stem and spinal cord), 74,75 the role of glycine in GABA/GHB neurons was not considered. To summarize, all these data support the existence, in GABAergic pathways, of common mechanisms that cosynthetize and coaccumulate GABA and GHB in presynaptic terminals, resulting in their corelease in mixed GABA/GHB synapses.…”
Section: A Synaptic and Plasma Membrane Transport Of Ghbmentioning
confidence: 99%
“…Initial studies showed that the inhibitory effects of GHB in the substantia nigra were not blocked by the GABA A receptor antagonist bicuculline (Olpe and Koella, 1979; Osorio and Davidoff, 1979). Later studies showed that the inhibitory effects of GHB on hippocampal and thalamocortical neurons were attenuated by selective GABA B receptor antagonists (Xie and Smart, 1992; Emri et al, 1996).…”
Section: Pharmacodynamics Of Ghbmentioning
confidence: 99%